A LINEAR PROGRAMMING APPROACH TO OPTIMIZING ENVIRONMENTAL RESOURCE MANAGEMENT IN URBAN AREAS - Idisi, Benjamin E.; Ogumeyo, S. A. (FUDMA JOURNAL OF SCIENCES, 2024)
This study investigates the optimization of environmental resource management in urban settings using a linear programming approach, focusing on ammonia production and wastewater management. The model addresses uncertainties in resource allocation by evaluating the cost implications of wastewater discharge during production. Key variables include water drawn from rivers, sludge discharge, and energy consumption. The study explores scenarios where zero-discharge policies are implemented, resulting in reduced water usage but increased energy consumption and higher production costs. The methodology employed linear programming to minimize the cost of ammonia production while ensuring water quality through regulated waste disposal. The findings indicate that minimizing river impurities through controlled waste discharge reduces water usage but escalates energy consumption, complicating cost management. Results from the numerical example show that under optimal conditions, 6,666.7 liters of water and 555.6 kg of sludge are needed to produce 41,666.7 kg of ammonia, with zero energy consumption in the process. The significance of these results lies in their potential to inform sustainable urban resource management policies that balance economic and environmental priorities. The study concludes that while achieving high water quality increases costs, it is crucial for sustainable ammonia production and environmental conservation, particularly in minimizing the ecological impact of industrial activities on water resources.